2019
DOI: 10.1371/journal.pone.0222568
|View full text |Cite
|
Sign up to set email alerts
|

The burden of oral conditions among adolescents living with HIV at a clinic in Johannesburg, South Africa

Abstract: BackgroundThere are inconsistent reports on the prevalence of oral conditions and their associated factors among adolescents living with HIV (ALHIV). The current inconsistencies may hinder the development of clear guidelines on the prevention and treatment of oral conditions among ALHIV. This study provides an update on oral conditions and their associated factors in a cohort of South African ALHIV and receiving routine HIV treatment services at a Johannesburg HIV wellness clinic.MethodsDecayed Teeth (DT), Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…Study showed that dental caries was also 1.5 times more among adolescents living with HIV who brush their teeth less frequently. 24 Caries was lowest in HIV-positive children who brushed their teeth at least twice a day. 25 Different articles have reported varied prevalence of caries in children with HIV infection.…”
Section: Discussionmentioning
confidence: 97%
“…Study showed that dental caries was also 1.5 times more among adolescents living with HIV who brush their teeth less frequently. 24 Caries was lowest in HIV-positive children who brushed their teeth at least twice a day. 25 Different articles have reported varied prevalence of caries in children with HIV infection.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of pseudomembranous candidiasis ranged from 1.7% in South Africa (56) to 72.2% in and Brazil (36). Also, the prevalence of angular cheilitis was highest in Indonesia, at 46.6% (3).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 4,057 individuals, 468 (11.53%) did not receive HAART or ART. The data from 11 articles (28,33,43,44,48,49,(51)(52)(53)(54)56) demonstrated that HAART or ART were significantly associated with reduction in oral Candida colonization or infection, while others showed the opposite relationship (12,16,32,34,41,42,55), or did not report any statistical data (11, 14, 26, 35-40, 47, 50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most common yeast causing oropharyngeal candidiasis ( Schoofs et al, 1998 ), but other non- albicans Candida species have also emerged in this context ( De Bernardis et al, 1996 ; Powderly et al, 1998 ; Cartledge et al, 1999 ; Mushi et al, 2016 , 2018 ; Ambe et al, 2020 ). Colonization of oral mucosal surfaces with yeasts such as C. albicans is closely correlated to symptomatic disease (oropharyngeal and esophageal candidiasis; Pappas et al, 2003 ) and latter one with the severity of cellular immunodeficiency, especially infected hosts with the HI virus ( Mercante et al, 2006 ; Malele Kolisa et al, 2019 ). In a resource-poor setting without access to CD4 + T-cell counting and HIV viral load measurements, oral candidiasis is one of the most important clinical markers of HIV infection, disease progression, CD4 + T-cell status ( Fidel, 2006 ; Berberi et al, 2015 ), and can even give a hint to antiretroviral therapy failure ( Hodgson and Rachanis, 2002 ; Ramirez-Amador et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%